SÍNTESE E CARACTERIZAÇÃO DE MEMBRANAS HÍBRIDAS MULTIFUNCIONAIS CONTENDO HIDRÓXIDOS DUPLOS LAMELARES INTERCALADOS COM NIMESULIDA PARA APLICAÇÃO ODONTOLÓGICA - Machado, Monielly Viomar (2024)
Considering the increase in life expectancy of the world population, the study of new materials that can act as alloplastic grafts and also have the characteristic of releasing drugs directly at the site of pain is considered of great importance. Thus, this work presents a study on the synthesis and characterization of hybrid membranes composed of biopolymers (alginate, chitosan and collagen) added with layered double hydroxides of zinc and aluminum interspersed with nimesulide, a non-steroidal anti-inflammatory. Such membranes have the potential to be used as resorbable grafts that release the drug in question more slowly. Presenting different synthesis methodologies for LDH Zn/Al and Mg/Al intercalated with Nimesulide and dispersed in the membrane produces a multifunctional composite, so that the variation of the synthesis method for LDH produced different morphologies for the final composite (granulated, three-dimensional porous and membrane). For the synthesis of the hybrid membrane, an experimental study was carried out with six variables to define the best composition for the synthesis of the membranes. The best condition presented was characterized by XRD, and subsequently a study on the release of nimesulide using UV-Vis spectroscopy was carried out. Release studies as a function of pH showed that LDH releases around 20% of the intercalated nimesulide at pHs above 2, while the membranes contribute to maintaining the nimesulide in its protonated form, not making it available to the environment, which contributes significantly, since this membrane, when used as a graft, will fulfill its structural function, and as it is absorbed by the body, it will release nimesulide into the focus of the patient's pain.